Sexual differences between biological presence and social construction - Alarabi HARRAN; Amal LOUALI (Social Sciences Journal, 2020)
Women are an essential element and a structural and functional member of the family and society. However, this important position of women has not prevented the existence of practices that degrade their value. Women today still suffer from domination and male domination as the best and honorable sex. The female gender is the lowest and the lowest, the male is born with a morphological structure and hormones that give him the power and the ability to dominate and dominate. The woman is born and is weak and has the ability to submit and surrender, But There are women who have been able to get out of this deficiency and compete with men and perhaps surpass them in the jobs and jobs that were the preserve of them, and therefore the origin of sexual differences is not sexual identity is gender - gender - this hierarchy between male and female is a social product within the framework of the system This is what the family has established through social upbringing where the girl is born to fear, humiliation and shame from natural things like her body, for example, as well as through various cultural rituals such as circumcision.